2013
DOI: 10.1016/j.jconrel.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Active self-healing encapsulation of vaccine antigens in PLGA microspheres

Abstract: Herein, we describe the detailed development of a simple and effective method to microencapsulate vaccine antigens in poly(lactic-co-glycolic acid) (PLGA) by simple mixing of preformed active self-microencapsulating (SM) PLGA microspheres in a low concentration aqueous antigen solution at modest temperature (10-38 °C). Co-encapsulating protein-sorbing vaccine adjuvants and polymer plasticizers were used to “actively” load the protein in the polymer pores and facilitate polymer self-healing at temperature > hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 44 publications
3
91
0
Order By: Relevance
“…Yet, one of the major drawbacks for the PLGA particle system has been the potential exposure of antigens to harsh organic solvents since conventional technique for loading antigens into PLGA particles involves formation of single or double emulsion (O/W or W/O/W) and solvent evaporation. However, with the recent advances in micro-encapsulation of biomolecules into pre-formed, self-healing PLGA particles, antigens can be loaded into PLGA vaccine particles in aqueous condition with minimal loss of their integrity and antigenicity (99,100). …”
Section: Synthetic Polymer-based Particlesmentioning
confidence: 99%
“…Yet, one of the major drawbacks for the PLGA particle system has been the potential exposure of antigens to harsh organic solvents since conventional technique for loading antigens into PLGA particles involves formation of single or double emulsion (O/W or W/O/W) and solvent evaporation. However, with the recent advances in micro-encapsulation of biomolecules into pre-formed, self-healing PLGA particles, antigens can be loaded into PLGA vaccine particles in aqueous condition with minimal loss of their integrity and antigenicity (99,100). …”
Section: Synthetic Polymer-based Particlesmentioning
confidence: 99%
“…The alternative to anhydrous encapsulation, which does not require micronization and organic solvents, is to remotely load the protein in preformed microspheres in water. This process has shown improvement in stability of lysozyme and tetanus toxoid [46,97,98] and is described below in Section 3.3.…”
Section: Approaches To Overcome Issues Impeding Depot Developmentmentioning
confidence: 99%
“…This is due to the loss of 3D structure and aggregation of immunogens during the synthesis of polymeric particles, which typically introduces organic solvents and high mechanical and/or chemical stresses to cargo materials [51]. New approaches to formulation of biologics into PLGA particles include a 'self-healing encapsulation' procedure that exploits the polymer's transition temperature to load antigens into preformed PLGA particles in an aqueous condition, thus avoiding the loss of their antigenicity and immunogenicity [52,53] On the other hand, recent studies have reported successful surface modification of recombinant Env trimers on synthetic lipid vesicles in an orientationspecific manner [54,55]. Using Ni-NTA-functionalized lipids, Env gp140 trimers with terminal polyhistidine tags (Histag) were anchored to the surfaces of interbilayer-crosslinked multilamellar vesicles (ICMVs).…”
Section: Synthetic Nanoparticles For Presentation Of Hiv-1 Antigensmentioning
confidence: 99%